Buletin Peternakan : PENGARUH PEMBERIAN MANURE AYAM PETELUR TERFERMENTASI DALAM PAKAN YANG DITAMBAH ORGANIC DEODORANT TERHADAP PERFORMA ITIK JANTAN UMUR 7-12 MINGGU - Djuriono (Peternakan UGM, 2015)
The research was conducted to analyze the effect of organic deodorant supplemented fermentedÃ‚ laying hens manure feeding on the performance of 7-12 weeks male ducks. One hundred 7 weeks old a male ducks were used to study the effetct MODF supplementation on performance of male ducks.